Topoisomerase I inhibitors – a unique class of antineoplastic agents - Deptała, Andrzej; Omyła-Staszewska, Joanna (Contemporary Oncology/Współczesna Onkologia, 2003)
Topoisomerase I inhibitors-analogues of alkaloid camptothecin, constitute a unique class of antineoplastic agents that have a broad spectrum of efficacy against various types of malignant tumors with acceptable toxicity. These drugs show an exceptional mechanism of action, stabilizing cleavable complexes consisting of topoisomerase I, covalently attached to DNA, which causes lethal genome damage during replication and transcription. Clinical studies have shown a broad spectrum of efficacy of semi-synthetic analogues of camptothecin–irinotecan (CPT-11) and topotecan (TPT), especially in colorectal cancer, small-cell, and non-small-cell lung cancer, cervical cancer, breast cancer, ovarian cancer, stomach cancer, pancreas cancer, liver cancer, renal cancer and head and neck cancer. In phase III studies, CPT-11 has demonstrated consistent objective antitumor activity in the treatment of advanced colorectal cancer. Therefore, the drug was established as a standard therapy in first-line as well as in second-line treatment (in patients refractory and/or relapsing after first line therapy) of colon cancer. Application of topoisomerase I inhibitors in therapy of small-cell lung cancer have also yielded promising results. In randomized phase III trial the median survival of patients suffering from advanced small-cell lung cancer, was significantly longer in irinotecan group comparing to standard chemotherapy. Topotecan is, in particular, active in advanced and recurrent ovarian cancer – both in platinum-sensitive and platinum-refractory cases. Topotecan also demonstrates high efficacy against esophageal cancer, cervical cancer, small-cell lung cancer, colon cancer, pancreatic cancer and acute myeloid leukemia. This comprehensive review summarizes the contemporary knowledge about the utility of topoisomerase I inhibitors in clinical oncology.